Mineralogical and geological investigation of Heraconpolis archaeological site, Upper Egypt - Pawlikowski, Maciej; Such, Joanna (My University, 2008)
The investigation of geology, stone implements and pottery presented below was performed in 2004 during works conducted by mixed american-egyptian mission at Heraconpolis archaeological site. The geological examination documents that the site was located on a dry, big delta of big wadi, coming from west into Nile Valley. This location means that while the site was functioning at phases Nagada II and III mentioned wadi did not conduct water i.e. climate was very dry. The investigation of present geological phenomena shows continuous growth of salinity of the soils at tested area. The investigation of stone implements discovered at two examined archaeological trenches confirmed the presence of various rocks, chipped flint implements as well as grinders. These objects were discovered at two depths representing various archaeological layers. Examination of pottery showed advanced technologies of preparation of ceramic mass as well as technology of firing. Data obtained from computer analyses confirm differentiation of tested ceramic masses.
Auxiliary Sciences in Archaeology, Preservation of Relics and Environmental Engineering
Załącznik: Short movie from Hierakonpolis.
Keywords: badania mineralogiczne; Nile Valley; badania geologiczne; geology; Egipt; mineralogy; dolina Nilu; stone implements; geologia; pottery; mineralogia